'Most of the Youth Are Drinking Because They Have Nothing to Do': How Idle Time Facilitates Adolescent Alcohol Use in Urban Tanzania. Issue 2 (3rd March 2020) - Carney, Allison; Kaaya, Sylvia; Kajula, Lusajo; Ibitoye, Mobolaji; Marwerwe, Graca; Sommer, Marni
Abstract: Societal factors influencing adolescent alcohol initiation and use are not well documented in Tanzania. The goal of this qualitative study was to explore the structural and environmental factors influencing adolescent alcohol uptake and use in urban Tanzania. 177 adolescents aged 15–19 from varying socioeconomic backgrounds participated in 16 participatory groups (separated by sex and in-school/out-of-school status) at sites in four different locations in Dar es Salaam, Tanzania. Participatory methods were used, including listing and ranking activities, and photovoice, exploring adolescent's perceptions around youth alcohol use, and recommendations for structural interventions to prevent or reduce adolescent alcohol uptake and use. Themes included: (1) "idle time" shapes adolescent alcohol use in urban Tanzania; (2) societal influences shape the locations where adolescents consume or purchase alcohol; and, (3) adolescents' recommendations about structural approaches for reducing their idle time and vulnerability to alcohol use. Our findings highlight the need for programs and policies aimed at reducing youth idle time as an approach to reducing alcohol use, such as increasing opportunities for employment, extracurricular activities, and entertainment, particularly for adolescent boys in urban Tanzania, given their increased vulnerability to the uptake and use of alcohol.